Hypoxia Aggravates Inactivity-Related Muscle Wasting - Debevec, Tadej; Ganse, Bergita; Mittag, Uwe; Eiken, Ola; Mekjavic, Igor B.; Rittweger, Jörn (Frontiers in Physiology, 2018)
Poor musculoskeletal state is commonly observed in numerous clinical populations such as chronic obstructive pulmonary disease (COPD) and heart failure patients. It, however, remains unresolved whether systemic hypoxemia, typically associated with such clinical conditions, directly contributes to muscle deterioration. We aimed to experimentally elucidate the effects of systemic environmental hypoxia upon inactivity-related muscle wasting. For this purpose, fourteen healthy, male participants underwent three 21-day long interventions in a randomized, cross-over designed manner: i) bed rest in normoxia (NBR; PiO2=133.1±0.3 mmHg), ii) bed rest in normobaric hypoxia (HBR; PiO2=90.0±0.4 mmHg) and ambulatory confinement in normobaric hypoxia (HAmb; PiO2=90.0±0.4 mmHg). Peripheral quantitative computed tomography and vastus lateralis muscle biopsies were performed before and after the interventions to obtain thigh and calf muscle cross-sectional areas and muscle fibre phenotype changes, respectively. A significant reduction of thigh muscle size following NBR (-6.9% SE 0.8%; P<0.001) was further aggravated following HBR (-9.7% SE 1.2%; P=0.027). Bed rest-induced muscle wasting in the calf was, by contrast, not exacerbated by hypoxic conditions (P=0.47). Reductions in both thigh (-2.7%, SE 1.1%, P=0.017) and calf (-3.3%, SE 0.7%, P<0.001) muscle size were noted following HAmb. A significant and comparable increase in type 2x fibre percentage of the vastus lateralis muscle was noted following both bed rest interventions (NBR=+3.1% SE 2.6%, HBR=+3.9% SE 2.7%, P<0.05). Collectively, these data indicate that hypoxia can exacerbate inactivity-related muscle wasting in healthy active participants and moreover suggest that the combination of both, hypoxemia and lack of activity, as seen in COPD patients, might be particularly harmful for muscle tissue.